1990
DOI: 10.1093/jpepsy/15.5.619
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Functioning of Children with Insulin-Dependent Diabetes Mellitus: A Longitudinal Study

Abstract: Assessed school-age youth repeatedly over the first 6 years of their insulin-dependent diabetes mellitus (IDDM) to determine self-perceived psychological adjustment. After the first year of IDDM, Ss exhibited a mild increase in depressive symptoms. Anxiety decreased for boys but increased for girls over the duration of IDDM. In contrast, self-esteem remained stable regardless of rehospitalizations or degree of metabolic control. Ss' adjustment shortly after IDDM onset, as reflected by levels of depression, anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
106
1
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 0 publications
6
106
1
3
Order By: Relevance
“…For example, Littlefield et al (9) found that adolescent girls not only exhibited poorer overall treatment compliance and metabolic control than boys, but that girls with poorer adherence also reported lower self-esteem, less self-efficacy, and more depressive symptoms. However, other studies (8,10,17) using similar methodologies have failed to demonstrate significant links between metabolic control and aspects of the self. In part, these inconsistent findings may result from the failure to consider the moderating role of gender on self-identity formation during adolescence.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Littlefield et al (9) found that adolescent girls not only exhibited poorer overall treatment compliance and metabolic control than boys, but that girls with poorer adherence also reported lower self-esteem, less self-efficacy, and more depressive symptoms. However, other studies (8,10,17) using similar methodologies have failed to demonstrate significant links between metabolic control and aspects of the self. In part, these inconsistent findings may result from the failure to consider the moderating role of gender on self-identity formation during adolescence.…”
mentioning
confidence: 98%
“…Compared with boys, girls have been shown to exhibit a constant increase in mean HbA 1c , with an estimated increase from pre-to postpuberty of 0.92% (6). Also, girls tend to be more distressed by diabetes (8), to exhibit higher rates of overall mismanagement of their diabetes (9) with less adherence to their diabetes meal plan during periods of stress (10), and to experience greater depressive and eating disorder symptoms, both of which are linked to poor metabolic control (9,11). Thus, there is a need to identify specific risk factors for poor metabolic control in girls.…”
mentioning
confidence: 99%
“…epression in children and adolescents with type 1 diabetes has been associated with negative diabetesrelated health outcomes such as poorer glycemic control (1)(2)(3)(4)(5) and recurrent diabetic ketoacidosis (DKA) admissions (6,7). While mechanisms that link depression and suboptimal health outcomes are poorly understood (8), it is apparent that the chronicity of type 1 diabetes and the demands of management provide a fertile environment for adjustment problems.…”
mentioning
confidence: 99%
“…Литература целиком базируется на краткосрочных наблюдениях за детьми и их семья ми [7,[10][11][12][13], и только в небольшой части проводят ся лонгитудинальные исследования. В результате этих изысканий были получены результаты, демон стрирующие, что дебют СД не имел выраженного влияния на психологическое состояние пациентов [14][15][16][17][18]. A.Jacobson и соавт.…”
Section: /21unclassified
“…[16] пока зали, что эмоциональные расстройства достаточно распространены, причем их наиболее высокий уро вень чаще всего наблюдается сразу после диагности ки СД. Для матерей с развившимся дистрессом сразу после выявления заболевания у детей характерен дли тельный период эмоциональной дисфории [18]. Это предполагает, что для успешной терапии подобных расстройств следует начинать терапию как можно раньше, во время начального обучения в школе диа бета [22].…”
Section: /21unclassified